Adaptasi Batang Pohon sebagai Sumber Ide Rias Fantasi Berbasis Mixed Media - Sofia Daniati; Nurulisma Saputri; Irene Fiolina (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
The development of fantasy makeup ideas is often used as a channel of expression in the growing field of makeup, as well as taking ideas from various sources that are often known as adaptations. The purpose of this study is to overcome the saturation of society towards conventional makeup and develop an understanding of the adaptation of fantasy makeup with mixed media-based tree theme. The method used in this study is the method of research and Development (Research and Development or R&D) with ADDIE development model. Based on the calculation results, it can be concluded that the color and visual composition, conformity with the theme and character, creativity and innovation, application techniques and neatness, visual impact and structure and composition have very good qualifications with a 93% achievement rate. Overall the final result of the product has a high aesthetic value and can be used as a reference in the field of makeup, especially fantasy makeup.